2018
DOI: 10.3892/etm.2018.6477
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokine gene polymorphisms with osteoarthritis susceptibility

Abstract: Osteoarthritis (OA) is a multifactorial disease characterized by low-grade inflammatory processes that are mediated initially by the cells and factors of the innate immune system. In addition to their key role in inflammation, cytokines contribute to the pathogenesis of OA through angiogenesis and chemotaxis. The purpose of the present case-control study was to investigate a possible association of four cytokine single nucleotide polymorphisms (SNPs), IL-4R -3223C>T (rs2057768), IL-8 -251T>A (rs4073), IL-10 -1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…Osteoartrithis (OA) is a form of arthritis that causes cartilage degeneration, especially in the elderly [56]. This chronic joint disease has as the main symptoms pain and stiffness due to the erosion of articular cartilage, bone remodeling, new bone formation, and synovial inflammation [57]. Rheumatoid arthritis is also associated with the time-span joint degradation, with symptoms such as articular cartilage erosion, synovial inflammation, and subchondral bone alterations, resulting in severe pain and impaired joint function [58].…”
Section: A Brief Overwiev Of Ostheoarticular Disordersmentioning
confidence: 99%
“…Osteoartrithis (OA) is a form of arthritis that causes cartilage degeneration, especially in the elderly [56]. This chronic joint disease has as the main symptoms pain and stiffness due to the erosion of articular cartilage, bone remodeling, new bone formation, and synovial inflammation [57]. Rheumatoid arthritis is also associated with the time-span joint degradation, with symptoms such as articular cartilage erosion, synovial inflammation, and subchondral bone alterations, resulting in severe pain and impaired joint function [58].…”
Section: A Brief Overwiev Of Ostheoarticular Disordersmentioning
confidence: 99%
“…So far, genome‐wide association studies have demonstrated that single nucleotide polymorphisms (SNPs) in a range of genes, such as growth differentiation factor 5 gene, Frizzled‐related protein gene, cartilage oligomeric matrix protein gene and chondroadherin‐like gene, and fat mass and obesity‐associated gene, are associated with susceptibility to OA. Apart from that, increasing literature elucidated a vital role of inflammation during the pathogenesis of OA, and various inflammatory cytokine genes which conferred susceptibility to OA are still being investigated . Among those inflammation‐related genes, evidence has been published for the association of interleukin‐17 ( IL‐17 ) SNPs and OA predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…It is a nonsteroidal antiinflammatory drug (NSAID) involved in the class of 2 aryl propionic acid (2-APA) that was first announced in England in 1967 (Davies, 1998). It inhibits the production of prostaglandins by decreasing the activity of the enzyme cyclooxygenase (Cole and Frautschy, 2010;Rogoveanu et al, 2018). Ibuprofen is also familiar for the advanced treatment of osteoarthritis, rheumatoid arthritis, ankylosing spondylitis, gout, and Bartter's syndrome (Kantor, 1979;Mititelu et al, 2020;Salehi et al, 2020).…”
Section: Ibuprofenmentioning
confidence: 99%